Organic Farming A Promising Way of Food Production - Konvalina, Petr (IntechOpen, 2016)
Organic farming is a progressive method of farming and food production it does not mean going back to traditional (old) methods of farming. Many of the traditional farming methods used in the past are still useful today. Organic farming takes the best of these and combines them with modern scientific knowledge. Authors' task was to write a book where many different existing studies could be presented in a single volume, making it easy for the reader to compare methods, results and conclusions. As a result, studies from different countries have been compiled into one book. I believe that the opportunity to compare results and conclusions from different authors will create a new perspective in organic farming and food production. I hope that our book will help researchers and students from all over the world to attain new and interesting results in the field of organic farming and food production.